Abnormal frontoparietal synaptic gain mediating the P300 in patients with psychotic disorder and their unaffected relatives. Issue 6 (27th March 2017) - Díez, Álvaro; Ranlund, Siri; Pinotsis, Dimitris; Calafato, Stella; Shaikh, Madiha; Hall, Mei‐Hua; Walshe, Muriel; Nevado, Ángel; Friston, Karl J.; Adams, Rick A.; Bramon, Elvira
Abstract: The "dysconnection hypothesis" of psychosis suggests that a disruption of functional integration underlies cognitive deficits and clinical symptoms. Impairments in the P300 potential are well documented in psychosis. Intrinsic (self‐)connectivity in a frontoparietal cortical hierarchy during a P300 experiment was investigated. Dynamic Causal Modeling was used to estimate how evoked activity results from the dynamics of coupled neural populations and how neural coupling changes with the experimental factors. Twenty‐four patients with psychotic disorder, twenty‐four unaffected relatives, and twenty‐five controls underwent EEG recordings during an auditory oddball paradigm. Sixteen frontoparietal network models (including primary auditory, superior parietal, and superior frontal sources) were analyzed and an optimal model of neural coupling, explaining diagnosis and genetic risk effects, as well as their interactions with task condition were identified. The winning model included changes in connectivity at all three hierarchical levels. Patients showed decreased self‐inhibition—that is, increased cortical excitability—in left superior frontal gyrus across task conditions, compared with unaffected participants. Relatives had similar increases in excitability in left superior frontal and right superior parietal sources, and a reversal of the normal synaptic gain changes in response to targets relative to standard tones. It was confirmed that both subjects with psychotic disorder and their relatives show a context‐independent loss of synaptic gain control at the highest hierarchy levels. The relatives also showed abnormal gain modulation responses to task‐relevant stimuli. These may be caused by NMDA‐receptor and/or GABAergic pathologies that change the excitability of superficial pyramidal cells and may be a potential biological marker for psychosis. Hum Brain Mapp 38:3262–3276, 2017 . ©2017 Wiley Periodicals, Inc.